Women's activism and globalization : linking local struggles and transnational politics - Naples, Nancy A.; Desai, Manisha (Routledge, 2002)
Women's Activism and Globalization is a broad and comprehensive collection that shows how women activists across the globe are responding to the forces of the "new world order" in their communities.